Determinants of willingness and ability to pay JKN contributions among traders at Gowa Regency, Indonesia - Salman, Muhammad; Arranury, Zilfadhilah; Surahmawati, Surahmawati (Community Research of Epidemiology (CORE), 2025)
The National Health Insurance (JKN) program is an effort to achieve Universal Health Coverage (UHC); however, independent participants still dominate inactive membership status due to contribution arrears. This study aimed to analyze the determinants of willingness and ability to pay JKN contributions among traders at Minasa Maupa Central Market, Gowa Regency. The population of this study consisted of all traders at Minasa Maupa Central Market totaling 1,102 people, with a sample of 204 respondents selected using accidental sampling. This study employed a quantitative approach with a cross-sectional design. Data were collected through structured questionnaires and analyzed using the chi-square test. The results showed a significant relationship between knowledge, income, perceptions of health services, and family support with willingness to pay JKN contributions, as well as a significant relationship between knowledge, income, perceptions of health services, and family support with the ability to pay JKN contributions. In addition, there was a significant relationship between willingness to pay and ability to pay JKN contributions. Conversely, there was no significant relationship between the number of family members and history of illness with either willingness or ability to pay JKN contributions. These findings indicate the need to improve health insurance education, strengthen family support, and implement contribution adjustment strategies to increase compliance among independent JKN participants.